2008
DOI: 10.1063/1.2822162
|View full text |Cite
|
Sign up to set email alerts
|

The role of short-ranged energetic correlations in the mobility field dependence of disordered organic materials

Abstract: We studied the mobility of charge carriers in a model for disordered organic solids where the energies of the localized states are Gaussianly distributed with short-ranged correlations. We obtained an expression for the mobility as a function of electric field, temperature, energetic variance, and correlation radius. The temperature dependence obtained with short-ranged energetic correlations is different from that obtained with power-law decaying energetic correlations and suggests a possible way to distingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…The difference between the eqs 2 and 4 is the predicted temperature dependence of γ. Recently, it has been shown that the form (short ranged or long ranged) of energy correlation can be distinguished from the temperature dependence of γ 25. However, the experimental data obtained in our study is unable to distinguish between the short range correlated energies and power‐law correlated energies as the parameter γ varies almost linearly with (σ/ kT ) as well as with $ (\sigma/kT) - 2 \sqrt{kT/\sigma} $ .…”
Section: Resultscontrasting
confidence: 72%
“…The difference between the eqs 2 and 4 is the predicted temperature dependence of γ. Recently, it has been shown that the form (short ranged or long ranged) of energy correlation can be distinguished from the temperature dependence of γ 25. However, the experimental data obtained in our study is unable to distinguish between the short range correlated energies and power‐law correlated energies as the parameter γ varies almost linearly with (σ/ kT ) as well as with $ (\sigma/kT) - 2 \sqrt{kT/\sigma} $ .…”
Section: Resultscontrasting
confidence: 72%
“…Lattice model calculations using the correlated Gaussian disorder model showed that a higher correlation length (coupling among sites which are far apart) leads to a steeper Poole-Frenkel slope. 66,67 Fig. 4 shows the reduced site energy correlation function…”
Section: Site Energy Correlationmentioning
confidence: 99%
“…8,9 Now that we have established the mechanism behind the correlation, what remains to be done is to calculate the mobility field dependence in a model of disordered sites with site energies given by the chargeinduced dipole interaction. …”
Section: Discussionmentioning
confidence: 99%